Organizational design as an enabler for innovation: evidence from a German Mechanical Engineering Company - Eisold, Sebastian (2009)
Over the past two decades there has been a profusion of empirical studies of organizational design and its relationship to efficiency, productivity and flexibility of an organization. In parallel, there has been a wide range of studies about innovation management in different kind of industries and firms. However, with some exceptions, the organizational and innovation management bodies of literature tend to examine the issues of organizational design and innovation management individually, mainly in the context of large firms operating at the technological frontier. There seems to be a scarcity of empirical studies that bring together organizational design and innovation and examine them empirically and over time in the context of small and medium sized enterprises. This dissertation seeks to provide a small contribution in that direction. This dissertation examines the dynamic relationship between organizational design and innovation. This relationship is examined on the basis of a single-case design in a medium sized mechanical engineering company in Germany. The covered time period ranges from 1958 until 2009, although the actual focus falls on the recent past. This dissertation draws on first-hand qualitative empirical evidence gathered through extensive field work. The main findings are: 1. There is always a bundle of organizational dimensions which impacts innovation. These main organizational design dimensions are: (1) Strategy & Leadership, (2) Resources & Capabilities, (3) Structure, (4) Culture, (5) Networks & Partnerships, (6) Processes and (7) Knowledge Management. However, the importance of the different organizational design dimensions changes over time. While for example for the production of simple, standardized parts, a simple organizational design was appropriate, the company needed to have a more advanced organizational design in order to be able to produce customized, complex parts with high quality. Hence the technological maturity of a company is related to its organizational maturity. 2. The introduction of innovations of the analyzed company were highly dependent on organizational conditions which enabled their introduction. The results of the long term case study show, that some innovations would not have been introduced successfully if the organizational elements like for example training and qualification, the build of network and partnerships or the acquisition of appropriate resources and capabilities, were not in place. Hence it can be concluded, that organizational design is an enabling factor for innovation. These findings contribute to advance our understanding of the complex relationship between organizational design and innovation. This highlights the growing importance of a comprehensive, innovation stimulating organizational design of companies. The results suggest to managers that innovation is not only dependent on a single organizational factor but on the appropriate, comprehensive design of the organization. Hence manager should consider to review regularly the design of their organizations in order to maintain a innovation stimulating environment.